End User Satisfaction of Accounting Information System (AIS) Mobile Based for Small Medium Enterprises (SMEs): Actual Usage and TAM Approach - Mardiana Andarwati; Diana Zuhroh; Fikri Amrullah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2019)
Increasing end-user satisfaction (EUS) on mobile-based AIS is influenced by an actual usage (AU). AU increases if Small Medium Enterprise managers feel the perceived ease of use (PEOU) and perceived usefulness (PU) of using mobile-based AIS. This study aims to (1) analyze the effect of PEOU and PU on AU, (2) analyze the effect of PEOU and PU on EUS on mobile-based AIS, (3) analyze the effect of AU on EUS on mobile-based AIS, and (4) analyze the effect of PEOU and PU to EUS on mobile-based AIS through AU. The results of this study are (1) PU has a positive effect on AU and PEOU has a negative effect on AU because to improve AU requires a guidebook that is easy to learn and the lack of ability to use system applications make it not easy, (2) PEOU and PU affect EUS on Mobile-based AIS but the most positive and dominant influence on EUS on mobile-based AIS is PU, (3) AU has a positive effect on EUS on mobile-based AIS, and (4) PEOU negatively affects EUS on mobile-based AIS through AU due to the use of AIS based on mobile, which is done repeatedly and for a long time is still unable to mediate PEOU and SME managers feel difficult to use the purchasing and sales system application to produce on time reports.